2020
DOI: 10.1080/0886022x.2020.1793353
|View full text |Cite
|
Sign up to set email alerts
|

Role of promoting inflammation of Krüppel-like factor 6 in acute kidney injury

Abstract: Background: Kr€ uppel-like factor 6 (KLF6) is a transcription factor that participate in various pathophysiological processes, but its contribution in ischemia acute kidney injury (AKI) is lacking so far. The study aimed to investigate the expression and the role of KLF6 in kidney ischemia-reperfusion (IR) injury. Method: Microarray data were collected from GSE58438 and GSE52004. The rat IR model was established to evaluate the mRNA and protein expression of KLF6 and inflammatory cytokines in serum and kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…KLF6 belongs to the zinc finger family and regulates the expressions of genes associated with signal transduction, cell cycle, and inflammation [37]. KLF6 participates in the mechanisms of AKI by elevating the levels of inflammatory cytokines [38]. Our results verified that circHIPK3 could upregulate the KLF6 level by competitively binding to miR-124-3p.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…KLF6 belongs to the zinc finger family and regulates the expressions of genes associated with signal transduction, cell cycle, and inflammation [37]. KLF6 participates in the mechanisms of AKI by elevating the levels of inflammatory cytokines [38]. Our results verified that circHIPK3 could upregulate the KLF6 level by competitively binding to miR-124-3p.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have elucidated that miR-124-3p, which can bind to circHIPK3, is poorly expressed in kidney injury [16, 36]. Next, the downstream genes of miR-124-3p were predicted, among which KLF6 is upregulated in kidney injury [37, 38]. Based on the binding sites between circHIPK3 and miR-124-3p, and miR-124-3p and KLF6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…26 KLF6 is highly expressed in kidney ischemia-reperfusion (IR) injury and can promote inflammation in acute kidney injury (AKI). 27 In this study, we down-regulated the expression of KLF6 in LPS-induced A549 cells and observed that down-regulated KLF6 could improve the viability, reduce the inflammatory response, and decrease the apoptosis of LPS-induced A549 cells.…”
Section: Cyr61 Overexpression Reversed the Inhibitory Effect Of Inter...mentioning
confidence: 78%
“…It is known that KLF15 is a member of the KLFs, which are a group of zinc-finger DNA-binding transcription factors involved in various biological processes, including cell differentiation, metabolism, inflammation, apoptosis, mitochondrial biogenesis and DNA repair [ 23 ]. Emerging evidence has demonstrated that KLFs also regulate key physiological and pathological processes in the kidney [ 24 ], some of them have been considered as early diagnosis biomarkers or therapeutic targets in AKI [ 25 ] and chronic kidney diseases [ 26 ]. Among the KLF family members, KLF15 is widely distributed in the glomeruli and in the proximal tubule.…”
Section: Discussionmentioning
confidence: 99%